2006
DOI: 10.1093/ndt/gfl094
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicentre study of the nutritional status in children on chronic peritoneal dialysis

Abstract: The anthropometry-bioimpedance analysis-nutrition (ABN) score is a recently proposed objective method of assessing malnutrition in children on chronic peritoneal dialysis (CPD) that uses nine parameters based on anthropometry, skinfold thickness and bioimpedance analysis. The aim of this prospective, cross-sectional study was to apply it to children treated with CPD in seven Italian paediatric nephrology centres, with a score of < 10.33 (the 3rd percentile in a population of 264 healthy children) classifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
1
33
2
2
Order By: Relevance
“…However, despite this, growth was maintained in our patients, without further decline in HtSDS after starting dialysis. Other reports of growth on dialysis vary from demonstrating an improvement in HtSDS [6,13]; to no change [14]; or to a fall in HtSDS [3]. Nevertheless, our results demonstrate that nearly 50% of our patients have a HtSDS<−2SD when entering our dialysis programme.…”
Section: Discussioncontrasting
confidence: 63%
“…However, despite this, growth was maintained in our patients, without further decline in HtSDS after starting dialysis. Other reports of growth on dialysis vary from demonstrating an improvement in HtSDS [6,13]; to no change [14]; or to a fall in HtSDS [3]. Nevertheless, our results demonstrate that nearly 50% of our patients have a HtSDS<−2SD when entering our dialysis programme.…”
Section: Discussioncontrasting
confidence: 63%
“…However, catch-up can occur, even on dialysis [47–49]. Poor nutritional status is associated with starting PD at a younger age [50]. Interestingly, infants who grew well continued with catch-up in early childhood [43, 47].…”
Section: The Epidemiology Of Nutritional Disturbances In Renal Diseasmentioning
confidence: 99%
“…Increasing severity of CRF adversely affects growth: when the patients were divided into those with a GFR greater or less than 25 ml/min/1.73 m 2 , the HtSDS was −1.65 and −2.79, respectively [44]. Reports of growth on dialysis vary from improvement [54], to no change [55] to declining HtSDS [56], with a worsening of nutritional status in children dialysed for more than a year [50]. …”
Section: The Epidemiology Of Nutritional Disturbances In Renal Diseasmentioning
confidence: 99%
“…Edefonti et al [85] proposed an anthropometry-bioimpedance analysis-nutrition (ABN) score based on nine anthropometry and BIA parameters, expressed as SDS and elaborated by means of a dedicated software program to calculate an ABN score that may vary from 3 to 15. Distribution percentiles were calculated in healthy children, and an ABN score of 10.33 was established as the low limit of normal (3rd percentile).…”
Section: Nutritional Management Of Children Receiving Maintenance Permentioning
confidence: 99%
“…Distribution percentiles were calculated in healthy children, and an ABN score of 10.33 was established as the low limit of normal (3rd percentile). A multicenter study on PD pediatric patients showed that 48.8 % of them had an ABN score lower than 10.33 as well as significantly lower levels of serum albumin, hemoglobin, and creatinine [85]. Therefore, the ABN score seems a valuable tool for monitoring nutritional status in children on chronic PD; further validation, however, is still needed.…”
Section: Nutritional Management Of Children Receiving Maintenance Permentioning
confidence: 99%